Incidence of microsatellite instability‐high hepatocellular carcinoma among Japanese patients and response to pembrolizumab. Issue 7 (6th March 2020) - Kawaoka, Tomokazu; Ando, Yuwa; Yamauchi, Masami; Suehiro, Yosuke; Yamaoka, Kenji; Kosaka, Yumi; Fuji, Yasutomo; Uchikawa, Shinsuke; Morio, Kei; Fujino, Hatsue; Nakahara, Takashi; Ono, Atsushi; et al.
Abstract : Aim: Pembrolizumab has been quickly approved in many countries for the treatment of patients with unresectable or metastatic, microsatellite instability‐high (MSI‐H) solid tumors, which have progressed following previous treatment and who have no satisfactory alternative treatment options. We aimed to determine the incidence of MSI‐H tumors in Japanese patients with advanced hepatocellular carcinoma (HCC). Methods: We investigated the incidence of MSI‐H tumors in 82 consecutive Japanese patients with unresectable HCC that had progressed after standard of care treatment. Using a companion diagnostic sequencing kit (polymerase chain reaction analysis of five microsatellite markers: BAT25, BAT26, NR21, NR24 and MONO27), we analyzed 49 biopsy specimens and 33 resection specimens. Responses to pembrolizumab were assessed with the modified Response Evaluation Criteria in Solid Tumors. Results: MSI‐H tumors were found in only two patients (2.4%), in whom all five markers showed slight shortening. One patient had a complete response to pembrolizumab for over 10 months, and the other was a non‐responder. Conclusions: MSI‐H tumor status was found in only two of 82 (2.4%) Japanese patients with advanced HCC, one of whom had a complete response to pembrolizumab. Thus, MSI status should be assessed in patients with HCC who progress after standard of care treatment.